Lack of an association between three tagging SNPs within the FTO gene and smoking behavior - Hubacek, Jaroslav A; Dlouha, Dana; Lanska, Vera; Adamkova, Vera (Nicotine & tobacco research, 2012)
INTRODUCTION: Using genome-wide screening, a polymorphism within the second intron of the FTO gene (rs2302673) was found to be associated with smoking habits in females. In a population-based, cross-sectional study, we analyzed three tagging FTO single-nucleotide polymorphisms (SNPs) for their association with smoking behavior. METHODS: Subjects from the Czech post-MONICA study, including 1,191 adult males (32.1% smokers) and 1,368 adult females (22.5% smokers) were included in this study. Smoking habits were obtained through questionnaire data analysis, and three FTO tagging SNPs were genotyped (rs17817449: intron 1, rs2302673: intron 2, and rs17818902: intron 3). RESULTS: We detected slightly lower frequencies (p = .043) of the GG genotype of the rs17818902 SNP in males who quit smoking compared with others. However, the significance disappeared after adjusting for multiple testing. Within the entire population, or in either males or females alone, we failed to detect a significant difference between other FTO genotypes and smoking status. Also, the number of cigarettes smoked per day was independent of individual FTO genotypes in both genders. CONCLUSIONS: We did not find an association between the FTO gene tagging variants and smoking status. FTO is unlikely to be a major genetic determinant of smoking status.
Keywords: tabákové výrobky; Genetic Predisposition to Disease; kouření; Cross-Sectional Studies; genotyp; jednonukleotidový polymorfismus; proteiny; Genotype; Česká republika; Middle Aged; průzkumy a dotazníky; mužské pohlaví; průřezové studie; Adult; Czech Republic; gen pro FTO; Smoking; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; ženské pohlaví; Humans; Surveys and Questionnaires; lidé středního věku; dospělí; genetická predispozice k nemoci; Female; Proteins; Tobacco Products; lidé; Male; Polymorphism, Single Nucleotide